PENINGKATAN POTENSI DESA KREATIF MELALUI SOSIALISASI INOVASI PRODUK USAHA KECIL DI DESA NANIA, KOTA AMBON - Aswad, Wa Ode Sitti Jurianti; Berhitu, Pieter Th.; Kesaulya, Hertine Megiestri; Rasyid, Risal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2024)
Creative village is an area located in a village/subdistrict administrative area where the community develops superior products in one or more of 17 creative economic sectors that provide additional value and benefits for village economic growth. In Ambon City, there are many countries/villages that have the potential to develop creative economic products, including Nania Village. Nania Village, especially Nania Gunung Village, has the potential to become a creative village, there are 19 families who own furniture businesses and are the center of furniture production in Ambon City. To increase the added value of the furniture business in Nania Gunung Village, it is necessary to encourage product innovation in the creative economy sub-sector, for example fine arts or high-value crafts. This service activity aims to provide understanding to the village government and business actors about the potential for developing small businesses in Nania Gunung Village through the creative economy sub-sector so that it can encourage the potential of Nania Village as a Creative Village. This community service activity is carried out using the door to door outreach method accompanied by observation, interviews and mentoring. The results of this activity are able to provide understanding to furniture business actors about product innovation so that some furniture business actors have used wood waste to make new craft products and have marketed products through the marketplace.